Association between oxidative stress and liver fibrosis severity in non-alcoholic fatty liver disease: insights from the pro-oxidant antioxidant balance method in a population from Tehran and Mashhad, Iran - Hami Ashraf; Hami Ashraf; Amir Anushiravani; Maryam Rayatpisheh; Daryoush Hamidi Alamdari; Arianaz Hossieni; Arianaz Hossieni; Behrang Kazeminezhad (Frontiers in Medicine)
BackgroundThe exact mechanisms of non-alcoholic fatty liver disease (NAFLD), recently redefined as metabolic dysfunction-associated steatotic liver disease (MASLD), remain unclear. However, oxidative stress is recognized as a factor across all stages of NAFLD. The Pro-oxidant Antioxidant Balance (PAB) method is an important clinical tool that provides an assessment of the balance between oxidants and antioxidant. We aimed to explore oxidative stress in NAFLD using the PAB method.MethodsIndividuals with NAFLD were recruited in 2021. Eligible participants underwent detailed assessments, including liver elastography for fibrosis evaluation. Blood samples (5 mL) were collected to measure serum PAB levels. The METAVIR score, derived from FibroScan measurements of liver stiffness, categorized fibrosis severity from F0 (no fibrosis) to F4 (advanced fibrosis or cirrhosis).ResultsThe study included 102 participants, with a mean age of 50.12 ± 10.03 years. Significant correlations were observed between FibroScan scores and variables such as age, body mass index (BMI), history of chronic diseases, and family history of NAFLD. PAB levels were notably higher in patients with advanced fibrosis (F2 and F3 groups: 86.32 ± 25.53) compared to those in early stages (F0 and F1 groups: 45.36 ± 21.29). Moreover, FibroScan scores showed a significant positive association with PAB values (odds ratio [OR]: 1.07; 95% confidence interval (CI): 1.04, 1.10), even after adjusting for confounding variables (OR: 1.13; 95% CI: 1.07, 1.18).ConclusionElevated PAB levels were strongly associated with advanced stages of liver fibrosis in NAFLD patients, reflecting increased oxidative stress with disease progression. These results highlight the potential of PAB as a marker for monitoring oxidative stress and disease severity in NAFLD. Nevertheless, further large-scale studies are warranted.